2018
DOI: 10.1159/000490092
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Phase II Study of Erlotinib for the Treatment of Patients with Relapsed/Refractory Acute Myeloid Leukemia

Abstract: Erlotinib, an epidermal growth factor receptor (EGFR) inhibitor, may have off-target activity inducing acute myeloid leukemia (AML) differentiation, possibly through SYK inhibition. We investigated erlotinib in a pilot phase II study for efficacy in relapsed/refractory AML patients at a dose of 150 mg once daily in 28-day cycles. Twenty-nine patients were treated for a median of 29 days (range 12–142 days). Seven patients (24%) received > 1 cycle of therapy and 12 (41%) discontinued treatment before day 28 due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…An inverse correlation between EREG expression and methylation was also observed in non-small cell lung cancers, head and neck cancers, and acute myeloid leukemias by examination of the TCGA data set [7]. These tumors are also indications for anti-EGFR therapies [23-26]. Recently, EREG expression as a predictive functional marker of sensitivity to anti-EGFR treatment was also reported in basal-like head and neck squamous cell carcinoma [27].…”
Section: Discussionmentioning
confidence: 92%
“…An inverse correlation between EREG expression and methylation was also observed in non-small cell lung cancers, head and neck cancers, and acute myeloid leukemias by examination of the TCGA data set [7]. These tumors are also indications for anti-EGFR therapies [23-26]. Recently, EREG expression as a predictive functional marker of sensitivity to anti-EGFR treatment was also reported in basal-like head and neck squamous cell carcinoma [27].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, another explanation for cross-tissue generalization can be the presence of drivers shared across cancer types. Different studies have identified pan-cancer driver genes across solid and non-solid tissues such as TP53, ERBB2, EGFR, or EML4-ALK (Mano 2008;Zapata et al 2017;Abou Dalle et al 2018;Bailey et al 2018;Joshi et al 2020). Interestingly, ERBB2 and EGFR are known to be associated with Erlotinib (one of the drugs we studied) that demonstrated cross-tissue generalization to non-solid tissues.…”
Section: Discussionmentioning
confidence: 94%
“…However, no evidence of direct binding by which these molecules induce phenotypic alterations in AML has been revealed. While multiple clinical trials using erlotinib or afatinib in AML have yielded con icting, but mostly negative clinical results 21,22,23,24 . Effective use of EGFRi in the treatment of AML patients has been stymied due to the absence of a method identifying the patients that might optimally bene t from this approach.…”
Section: Introductionmentioning
confidence: 99%